Effect of tuber skin on the thermal properties of whole tubers of potato and sweet potato - Oluwo, A A; Khan, Md. Raisuddin; Salami, Momoh Jimoh Emiyoka (IOP Publishing, 2014)
Temperature-dependent thermal coefficients of mathematical models of the postharvest storage process play an important role in determining the models accuracy. Thermal properties of tubers under storage available in literature are generally of those in semi processed form (skinless) such as those having undergone peeling, dicing and cutting actions. This study investigates the effect of tuber skin on the thermal properties of whole tubers of potato and sweet potato. A direct approach was used to measure the tubers' density and thermal conductivity and thermal diffusivity by the transient heat transfer method. Indirect approach was used to measure the tubers' specific heat. Experimental data were used to develop empirical models of the thermal coefficients as a function of temperature. Results of the study should find great use in the modeling of potato and sweet potato storage process.